The Effectiveness of Biofeedback Using Heart Rate Variability (HRV) on Working Memory Performance in Children with Attention Deficit/Hyperactivity Disorder (ADHD) - Asbaghi, Mona; Arjmandnia, Aliakbar; Hasanzadeh, Saeed; Rostami, Reza; Pourkarimi, Javad (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The present study aimed to investigate the effectiveness of a biofeedback intervention program using heart rate variability (HRV) on working memory performance in children with Attention Deficit/Hyperactivity Disorder (ADHD).Methods and Materials:  In this quasi-experimental study, a total of 30 children aged 8 to 12 years were selected through convenience sampling from clinics and counseling centers in District 3 of Tehran during 2021-2022 and were included in the study. Participants were randomly assigned to either the experimental group (15 participants) or the control group (15 participants). The experimental group participated in 15 sessions of a biofeedback intervention program using HRV, while the control group was placed on a waiting list without receiving any intervention. The working memory performance of both groups was assessed at the pre-test and post-test stages using the n-back working memory test, introduced by Kirchner in 1958. The data were analyzed using univariate analysis of covariance.Findings:  The results indicated the effectiveness of the biofeedback intervention program using HRV on the working memory performance of children with ADHD.Conclusion:  Overall, this study provides preliminary evidence for the use of HRV biofeedback as a potential intervention to improve working memory performance in children with ADHD, although further research is needed to confirm these findings.